`Socio-Demographic Association with Nutritional Status in Children Aged 8-9 Years Old in Surabaya: Focusing on HAZ Status in Path Analysis - Ardianah, Eva; Indriani, Diah; Soenarnatalina, Melaniani; Widjaja, Nur Aisiyah; Santoso, Febrina Mustika (Universitas Airlangga, 2025)
Background: Child health, growth, and nutrition are influenced by socioeconomic, cultural, demographic, climatic, nutrition, physical, hygiene, sanitation, medical, and environmental factors. LAZ/HAZ was used to assess the presence of 'stunting' in the population, which indicates chronic malnutrition. Objectives: to investigate the socio-demographics, lifestyle (sleep duration, screen time) and HAZ status of children in 2nd and 3rd grade of elementary school, and the correlation of socio-demographics with the anthropometric parameters. Methods: An observational study with a cross-sectional design was conducted during October – December 2022 in Surabaya, involving healthy children aged 9-10 years old who were in 2nd and 3rd grade of elementary school. Results: BMI-for-age z-score was higher in males than females. Overweight/obesity were prevalent in males (15.16% vs. 10.67%), and underweight and severely underweight were prevalent in females (12.27% vs. 14.23%). The prevalence of stunted/severely stunted was 12.39%. HAZ and WAZ were correlated positively with parental height. The number of children in the household had a negative, weak correlation with HAZ. The maternal education showed that the prevalence of maximal elementary school graduation was higher in stunted children than in normal children (29.27% vs. 18.14%, p=0.043). Fathers' salaries below minimum regional wage were more prevalent among stunted and severely stunted (81.71% and 75%, respectively) than normal subjects (60%), p=0.007. Conclusion: Socio-demographic factors affecting the prevalence of stunting in children were the father's salary and maternal education. Meanwhile, factors associated with HAZ were parental height and number of children in the household. The effect of socio-demography on HAZ was mediated by parental education, which stimulates household economics and has a further effect on food intake and child anthropometrics.